KESETERAAN GENDER DALAM BUDAYA PATRIARKI PADA MASYARAKAT HINDU BALI - i wayan, ariyarta; I Wayan Putu Sucaya Aryana; Cokorde Istri Dian Laksmi Dewi (VYAVAHARA DUTA, 2024)
The issue of gender equality remains a classic problem in society, as concepts of gender equality struggle seem to dissipate under the strong influence of patriarchal culture. Bali, as one of the regions with customary law society adhering to patriarchal culture, reflects patriarchy through the concept of Purusa in the kinship system of Hindu Balinese society. The Purusa concept is one of the roots of the difficulty in achieving gender equality in Hindu society. The purpose of this article is to understand the influence of patriarchal culture on the development of gender equality in modern society today. The method used in writing this article is normative writing method using literature study approach.   The strong phenomenon of patriarchy in Balinese Hindu society is almost undeniable, resulting in Balinese women still occupying a lower position than men. This research is expected to provide insights into the strength of patriarchal culture in Balinese Hindu society, which impacts the disadvantaged position of Balinese women in household environments, employment, and social settings. Moreover, patriarchy also contributes to high levels of violence, including physical, psychological, and sexual violence.